2016
DOI: 10.3947/ic.2016.48.4.338
|View full text |Cite
|
Sign up to set email alerts
|

Severe Fever with Thrombocytopenia Syndrome Presenting with Hemophagocytic Lymphohistiocytosis

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne disease caused by the newly discovered SFTS Bunyavirus, and there have been no case reports of SFTS patients presenting with hemophagocytic lymphohistiocytosis (HLH) in the English literature. We report a case of SFTS presenting with HLH in a 73-year-old immunocompetent male farmer. Although the patient had poor prognostic factors for SFTS, such as old age and central nervous system symptoms, he recovered fully with supportive care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…24,25 Meanwhile, cytokine storm can contribute to hemophagocytic lymphohistiocytosis (HLH). 4,26 Takahashi et al reported that five SFTS patients who underwent bone marrow aspirate, all exhibited hemophagocytosis which was also observed in lymph nodes and spleen. 4 Jung et al suggested SFTS cases complicated by HLH have a worse prognosis.…”
mentioning
confidence: 99%
“…24,25 Meanwhile, cytokine storm can contribute to hemophagocytic lymphohistiocytosis (HLH). 4,26 Takahashi et al reported that five SFTS patients who underwent bone marrow aspirate, all exhibited hemophagocytosis which was also observed in lymph nodes and spleen. 4 Jung et al suggested SFTS cases complicated by HLH have a worse prognosis.…”
mentioning
confidence: 99%
“…Patients with severe SFTS might experience hemophagocytic lymphohistiocytosis, which associated with cytokine storm ( Lee et al., 2016 ; Oh et al., 2016 ; Nakano et al., 2017 ; Kaneko et al., 2018 ; Kim et al., 2018 ; Jung et al., 2019). Hemophagocytic lymphohistiocytosis was characterized by persistent activation of CTLs, NK cells, and macrophages and was often accompanied with uncontrolled abnormal secretion of inflammatory cytokines, resulting in systemic inflammatory symptoms and signs ( Al-Samkari and Berliner, 2018 ).…”
Section: Host Immune Responsementioning
confidence: 99%